Utilising biomass for renewable energy production: Optimal profitability evaluation from different processing routes - Abdul Halim, Abdul Razik; Mohd Zulkifli, Mohamad Noor; Muhamad Fariz, Failaka; Elkamel, Marwen; Elkamel, Ali (Faculty Mechanical Engineering, UMP, 2017)
Utilisation of biomass such as wheat straws for the renewable energy production is an attractive option for agricultural diversifications and sustainability targets. One of the possible energy products from wheat straws is bioethanol. Since bioethanol could be produced from different ways, the issue arises on how to select the most economical one. In this paper, four processing routes to convert the wheat straws into bioethanol were screened; i) pelletisation and gasification, ii) torrefied pelletisation and gasification, iii) dilute acidic hydrolysis and fermentation, and iv) concentrated acidic hydrolysis and fermentation. The objective was to develop optimisation models to evaluate these routes as find the one that would produce the highest annual profitability by considering the whole supply chain. A mathematical model for optimisation, classified as linear programming, was then formulated to consider the biomass blending requirements and profitability equation. Optimisation results showed that the conversion of wheat straws into bioethanol could be potentially exploited via the torrefied pelletisation and gasification route as they gave the highest profitability of $489,330 per year, in the view of the whole supply chain. This was followed by concentrate acidic hydrolysis and fermentation route of $ 472,500 per year, dilute acidic hydrolysis and fermentation route of $402,750 per year, and pelletisation with gasification route of $388,530 per year. The developed optimisation models have been successfully screened and selected the best processing route to produce bioethanol from the evaluated profitability. Since this was at the conceptual stage, further refinement of the model parameters will be needed to provide a more practical basis for comparison.